Evaluating the content and development of decision aid tools for the management of menopause: A scoping review. (December 2017) - Siyam, Tasneem; Sultani, Humirah; Ross, Sue; Chatterley, Trish; Yuksel, Nese
Highlights: The first scoping review to evaluate the quality of content and development of decision aid tools for managing menopause. Less than half of decision aid tools were informed by the decisional needs of menopausal women. None of the decision aid tools reported steps involved in finding, appraising and summarizing scientific content of the tool. The lack of peer-reviewed, evidence-based decision aid tools for managing surgical menopause is emphasized. A decision aid tool to help women manage symptoms of surgical menopause should be considered. Abstract: Objective: Decision-making during menopause (especially surgical menopause) can be complex given the variability in risk–benefit perceptions of menopausal treatments. Decision aid tools (DATs) help women participate in decision-making about options. Our objective is to identify and evaluate the content and development of DATs for managing menopause, with a special focus on surgical menopause. Methods: We systematically searched electronic databases, including MEDLINE and EMBASE, from inception to March 2017 for relevant records. The principal inclusion criterion was that papers reported studies on DATs for managing menopause. Search terms were derived from two concepts: menopause and DATs. Data extracted were presented in written evidence tables and narrative summaries. Results: Our search yielded 18, 801 records. Of these, 26 records met our inclusion criteria, which gave rise to 12 DATs from peer-reviewed literature and 6 from grey literature. Seventeen DATs were focused on natural menopause and two targeted surgical menopause, both identified from grey literature. More than half were published before the Women's Health Initiative (WHI) publication and 70% before the release of the International Patient Decision Aid Standards (IPDAS). Very few studies reported the full development of the DAT involved, and less than half of DATs were informed by a needs assessment to identify the decisional needs of their target population. Most DATs focused on hormone therapy as a treatment option and did not provide a comprehensive overview of other options. None of the DATs reported the steps involved in finding, appraising and summarizing scientific content of the tool. Conclusion: This review highlights several limitations in the content and development of DATs for managing menopause. No peer-reviewed DATs were identified for surgical menopause. A need for a complete, evidence-based DAT in the context of surgical menopause is identified.